Application of a Rational Emotive Behavioral Approach in Group Counseling in an Educational Setting - Diah Rusdayanti, I Gst. Agung; Suranata, Kadek; Suarni, Ni Ketut (International Journal of Applied Counseling and Social Sciences, 2023)
The rational emotive behavioral approaches as one of the curative services through group counseling in schools that can alleviate problems faced by learners in an educational setting aims to help learners improve and change perceptions, ways of thinking, and irrational beliefs from the perception of the perspective on the problem to more flexible and rational (realistic) beliefs and more adaptive changes in the behavioral and emotional consequences experienced, to develop themselves and achieve optimal self-realization. The method used in this study is a literature review. The purpose of this study is to find out psychological problems in education that can be intervened with counseling through the rational approach of behavioral emotive, knowing the stages of implementing group counseling with a rational emotive behavioral approach, and the application of the rational emotive behavioral approach in group counseling in an educational setting. Psychological problems in education that can be intervened with counseling through a rational emotive behavioral approach are problems of aggression, anxiety, negative thinking, perfectionism, low self-esteem, low self-confidence, emotional disorders, learning disabilities, low academic achievement, and academic performance. The process of implementing group counseling with a rational emotive behavioral approach in educational settings is carried out with the main stages adjusted to ABCDE theory, namely the beginning stage, middle stage, and an ending stage. The application of a rational emotive behavioral approach in group counseling in an educational setting is the counseling of groups into responsive services in helping students who experience difficulties who need to be assisted in identifying problems, finding alternative problem-solving, and making decisions.